2021
DOI: 10.1097/hjh.0000000000003052
|View full text |Cite
|
Sign up to set email alerts
|

Does severe subacute noise exposure increase risk of new onset hypertension beyond conventional risk factors? A 30 000 person-years cohort study

Abstract: Objectives: Previous studies mostly focused on the relationship between chronic environmental noise exposure and hypertension but the effects of subacute (under 4 years) exposure with severe (>85 dB) noise exposure on clinical level hypertension have not been explored. This study aimed to reveal the association between severe noise exposure and hypertension. Methods: The severe noise exposure group was recruited from a Common Data Model conducted for the Korean Participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…However, research on the relationship between occupational noise exposure and hypertension is ambiguous. 5 , 6 , 7 , 8 , 9 , 10 , 11 Several studies have confirmed that occupational noise exposure may be a risk factor for hypertension 6 , 7 , 8 , 11 ; however, some studies reported no association between the two. 9 , 10 A prospective study including 578 male workers from an aircraft manufacturing plant in Taiwan investigated the relationship between noise exposure and the 10‐year risk of hypertension and found that prolonged exposure to occupational noise levels ≥85 dBA (A‐weighted decibels) may increase blood pressure levels in men.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, research on the relationship between occupational noise exposure and hypertension is ambiguous. 5 , 6 , 7 , 8 , 9 , 10 , 11 Several studies have confirmed that occupational noise exposure may be a risk factor for hypertension 6 , 7 , 8 , 11 ; however, some studies reported no association between the two. 9 , 10 A prospective study including 578 male workers from an aircraft manufacturing plant in Taiwan investigated the relationship between noise exposure and the 10‐year risk of hypertension and found that prolonged exposure to occupational noise levels ≥85 dBA (A‐weighted decibels) may increase blood pressure levels in men.…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the relationship between occupational noise exposure and hypertension is ambiguous 5–11 . Several studies have confirmed that occupational noise exposure may be a risk factor for hypertension 6–8,11 ; however, some studies reported no association between the two 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…This may damage the future health of veterans. A study found that ex-smokers developed hypertension at a rate of 52% more than non-smokers, and smokers developed hypertension at 26% more than non-smokers (Yun et al, 2022). On the contrary, some studies stated that smoking alone is a risk factor for the development of hypertension (Suzuki et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Факт обнаружен при проведении предварительного медицин-ского осмотра. Необходимо продолжать профилактические программы Выявленные результаты нашего исследования подтверждаются другими похожими исследованиями, сложностью которых является определение выборки по факторам риска ХНИЗ [7,20,[31][32][33][34].…”
Section: Discussionunclassified
“…Кардиоваскулярный риск играет важную роль в пациентоориентированной профилактике работающих. По некоторым данным отмечается влияние на него вибрации, шума, низких температур, инженерных наночастиц из промышленного аэрозоля [11,19,24,31]. При проведении пациентоориентированной профилактики мы выявили, что два визита к специалисту в условиях цехового здравпункта значительно влияют на снижение кардиоваскулярного и профессионального рисков [33].…”
Section: Discussionunclassified